3x +
5x -
2 =02x²+5x+2 2x²+11x+2 3{2x²+5x+2≠0{2x²+11x+2≠02x²+5x+2≠0D=25-4*2*2=25-16=9x₁≠
-5-3 = -2 4x₂ ≠
-5+3 = -1/2 42x² +11x+2≠0D=121-4*2*2=121-16=105x₁≠
-11 -√105 4x₂ ≠
-11+√105 4{x≠-2{x≠-1/2{x=
-11-√105 4{x=
-11+√105 4Делим числители и знаменатели первых двух дробей на х, учитывая, что х≠0:
3х/x +
5x/x -
2 =02x²/x +5x/x +2/x 2x²/x +11x/x +2/x 3
3 +
5 -
2 =0 2x +5 +2/x 2x +11 +2/x 3
3 +
5 -
2 =02x +2/x +5 2x+2/x+5+6 3Обозначим через у=2x +2/x+5
3 +
5 -
2 =0 y y+6 3y≠0 y≠ -6Общий знаменатель: 3у(у+6)3*3(y+6)+5*3y -2y(y+6)=09y+54+15y-2y²+12y=0-2y² +12y +54=0y² -6y -27 =0D=36+4*27=36+108=144y₁ =
6 -12 = -3 2y₂ =
6+12 =9 2При у=-32x+2/x+5=-32x +2/x+5+3=02x² +2 +8x=0x² +4x+1=0D=16-4=12x₁=
-4 -√12 =
-4 - 2√3 = -2 -√3 2 2x₂ =
-4 +√12 = -2 +√3 2При у=92x +2/x+5=92x+2/x+5-9=02x+2/x-4=02x²+2-4x=0x² -2x +1=0(x-1)² =0x=1Ответ: -2 -√3; -2 +√3; 1.